Changes in indicators of well-being on moving from home to long-term care for Māori in Aotearoa New Zealand: A retrospective cohort study - Hikaka J; Abey-Nesbit R; Wu Z; Jamieson HA; Parsons M; Kerse N; Gibson R (John Wiley & Sons Australia, Ltd on behalf of AJA Inc., 2024)
OBJECTIVE: To investigate changes in well-being measures for older Māori after moving from community to long-term care (LTC). METHODS: We undertook a retrospective cohort study of older Māori in New Zealand (NZ) who had received assessments for their health needs whilst living at home (interRAI-HC assessment) as well as a subsequent assessment after moving into a care facility (interRAI-LTCF). All interRAI-HC assessments from 01 July 2013 to 21 December 2018 were identified and matched to LTCF assessments that were undertaken at least 6 months later. Odds ratios (OR) and 95% confidence interval (CI) were calculated to determine the difference in proportion of variables of interest (indicative of movement, socialising, sleep and nutrition, alongside general physical and mental health status) between participants' HC and subsequent LTCF assessments. RESULTS: Changes in well-being measures were investigated among 1531 Māori (mean age 76.2 years, 61% female). Odds of having a fall (OR: 0.40 [95% CI 0.34, 0.48]), being lonely (OR: 0.13 [95% CI 0.09, 0.18]), sleeping difficulty (OR: 0.74 [95% CI 0.60, 0.91]) and fatigue (OR: 0.18 [95% CI 0.14, 0.23]) reduced on moving to LTC. However, the presence of depression (OR 3.96 [95% CI 2.58, 6.09]) and dependence with locomotion (OR 1.56 [95% CI 1.23, 1.97]) significantly increased when moving from home to LTC. CONCLUSION: Despite some indicators of functional and health-related decline, significant improvements are also apparent across multiple domains of well-being. Further investigation of resident and family perceptions of well-being in association with a move to LTC is warranted.
Keywords: health services; home care services; indigenous; long‐term care